2022
DOI: 10.11613/bm.2023.010706
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of melatonin concentration in preterm infants and adverse outcomes in the late neonatal period

Abstract: Introduction:The aim of research was to assess the melatonin concentrations in the early neonatal period as a predictor of adverse outcomes of late neonatal period in preterm infants and to estimate its optimal predictive cut-off values. Materials and methods: A total of 115 preterm infants admitted to the neonatal intensive care unit were screened for eligibility, five did not meet the criteria, six parents declined the participation. So, a total of 104 preterm infants with gestational age 25-34 weeks were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Since ME is an active bio component of human milk with concentrations higher at night, the newborn can take advantage of breastfeeding 19 . Although the use of ME as a neuroprotector appears to be a promising strategy in preterm infants, few recent studies tested the effect of ME administration on the clinical outcome in preterm populations 21,22 . By contrast, several trials reported the effectiveness of ME administration in term newborns suffering from hypoxic‐ischemic encephalopathy 23–25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ME is an active bio component of human milk with concentrations higher at night, the newborn can take advantage of breastfeeding 19 . Although the use of ME as a neuroprotector appears to be a promising strategy in preterm infants, few recent studies tested the effect of ME administration on the clinical outcome in preterm populations 21,22 . By contrast, several trials reported the effectiveness of ME administration in term newborns suffering from hypoxic‐ischemic encephalopathy 23–25 …”
Section: Introductionmentioning
confidence: 99%
“…19 Although the use of ME as a neuroprotector appears to be a promising strategy in preterm infants, few recent studies tested the effect of ME administration on the clinical outcome in preterm populations. 21,22 By contrast, several trials reported the effectiveness of ME administration in term newborns suffering from hypoxic-ischemic encephalopathy. [23][24][25] Our study aimed to assess: (i) the endogenous ME production in very preterm infants (gestational age, GA ≤ 29 + 6 WE) measuring plasma concentration within 96 h from birth; (ii) plasma ME availability and its metabolization to the main metabolite 6-OH-ME after 15 days of oral ME treatment (3 mg/kg/day or equivalent placebo); (iii) MDA plasma concentrations in the ME and the placebo groups.…”
mentioning
confidence: 99%